TEACHING WRITING ANALYTICAL EXPOSITION TEXT BY USING TEAM WORD-WEBBING TECHNIQUE - Yudianto, Fajar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The purpose of this research was to investigate whether or not the use of ?Team Word-Webbing Technique? effective in teaching writing analytical exposition text at the eleventh grade students of SMAN 1 Sungai Ambawang in academic year 2016/2017. This research applied a quasi-experimental design. The population of this research was XI IPA 2 as the experimental group and XI IPA 1 as the control group. The data was collected by using measurement technique with written test as the tool of collecting data. The research findings showed that the mean score of pre-test in the experimental group was 30.25, while the mean score of post-test was 66.71. On the other hand, the mean score of pre-test in the control group was 28.15, while mean score of the post-test was 56.03. The computation result by using t-test showed the value of t-test was 6.34 with df 62 in the significance degree of 5%, t-table was 1.99897, it meant that t-test was higher than t-table. Furthermore, the effect size of treatment was 0.65 which was classified as ?moderate?. Thus, the significant difference could be interpreted that the use of team word-webbing technique was effective in improving the students? ability in writing analytical exposition text. Keywords: Analytical Exposition Text, Teaching Writing, Team Word-Webbing.